2021
DOI: 10.1371/journal.pone.0246542
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and effective verbal communication in Peruvian children: A secondary analysis of the 2019 Demographic and Health Survey

Abstract: Background To estimate the impact of stunting on the development of effective verbal communication (EVC) in children aged 24 to 36 months. Methods We conducted a retrospective, quasi-experimental study design using data from 4452 children between 24 and 36 months of age available in the Early Childhood Development (ECD) section of the Demographic and Family Health Survey (ENDES) 2019 survey. Achievement of EVC was considered as the dependent variable. After propensity score matching analysis, a total 601 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…98 In contrast, the practice of brushing teeth with fluoridated dentifrices has been widespread in Latin American countries since childhood. [99][100][101][102] However, some studies have suggested that this habit begins later and occurs less frequently among families with lower socioeconomic status. [103][104][105] Table 2 shows some trials on the behavioral risk factors and caries in LACC.…”
Section: Regular Preventive Dental Carementioning
confidence: 99%
“…98 In contrast, the practice of brushing teeth with fluoridated dentifrices has been widespread in Latin American countries since childhood. [99][100][101][102] However, some studies have suggested that this habit begins later and occurs less frequently among families with lower socioeconomic status. [103][104][105] Table 2 shows some trials on the behavioral risk factors and caries in LACC.…”
Section: Regular Preventive Dental Carementioning
confidence: 99%
“…However, intense health counselling can increase the understanding of under-tax mothers regarding stunting and nutrition of under-fives. Parental education and socioeconomic factors affect energy and protein intake in under-fives who have edited [13,25].…”
Section: Discussion the Effectiveness Of Ipc Against Attitudes About Stuntingmentioning
confidence: 99%
“…The study results showed a relationship between the birth length of toddlers, history of exclusive breastfeeding, family income, mother's education, and maternal nutrition knowledge on the incidence of stunting in toddlers. Therefore, integrated and multisectoral programs are needed to increase family income, education, nutrition knowledge, and exclusive breastfeeding in reducing stunting [11][12][13][14][15][16][17]. low family economic status is a significant risk factor for stunting in toddlers aged 2-3 years [4,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La ENDES mide la hemoglobina en niños(as) de 6 a 35 meses y recoge información sobre características del cuidado del niño(as) y sociodemográficas que pueden ser covariables en la asociación entre anemia y la CVE 6,15,16 . En el Perú, estos datos han permitido estimar el efecto de la desnutrición crónica sobre la CVE 17 , sin embargo, no se ha estudiado el efecto de la anemia sobre la CVE. Ante la reducida muestra de estudios previos, que pudo afectar su capacidad para identificar asociaciones; y según el principio de analogía, sustentado por la existencia de efectos negativos de la anemia en otras dimensiones del desarrollo psicomotor en niños(as), formulamos esta investigación.…”
Section: Introductionunclassified